2018
DOI: 10.1002/anie.201812779
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed [3+2] Cycloaddition Reactions of Isocyanoacetates with Phosphaalkynes to Prepare 1,3‐Azaphospholes

Abstract: A novel copper‐catalyzed synthetic method is described for phosphorous‐ and nitrogen‐containing heterocycles such as 1,3‐azaphospholes. Cycloaddition reactions of various isocyanoacetates with phosphaalkynes in the presence of copper bromide, bis(diphenylphosphino)methane (dppm), and potassium carbonate afford the corresponding 1,3‐azaphospholes in high yields with complete selectivity. Some dppm‐bridged dicopper complexes were identified as active species for the formation of 1,3‐azaphospholes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…The training set used in this study is composed of 21 molecules containing C-P bonds for which experimental 1 J CP values have been reported: 5 with a C-P single bond, 56,57 6 with a double bond, [57][58][59][60][61][62] and 10 with a triple bond (see ESI † for more details). [63][64][65][66][67][68][69] Originally, exploring empirical corrections for a broader dataset of 1 J XY coupling-constant data, where X and Y are C, N, or P, was intended. However, unlike the coupled cluster data reported by Del Bene and coworkers, 41 experimental and computed DFT data for this level of atom generality were too poorly correlated for meaningful linear regression.…”
Section: Methodsmentioning
confidence: 99%
“…The training set used in this study is composed of 21 molecules containing C-P bonds for which experimental 1 J CP values have been reported: 5 with a C-P single bond, 56,57 6 with a double bond, [57][58][59][60][61][62] and 10 with a triple bond (see ESI † for more details). [63][64][65][66][67][68][69] Originally, exploring empirical corrections for a broader dataset of 1 J XY coupling-constant data, where X and Y are C, N, or P, was intended. However, unlike the coupled cluster data reported by Del Bene and coworkers, 41 experimental and computed DFT data for this level of atom generality were too poorly correlated for meaningful linear regression.…”
Section: Methodsmentioning
confidence: 99%
“…A small amount of isomeric product (3a' ')w as observed when dppe,PPh 3 ,and dtbpy were used as ligands (entries 6, 8, and 9). Finally,w ec onfirmed that the combination of CuBr, dppm, and K 2 CO 3 is necessary to obtain 3a in good yield (entries [10][11][12].…”
mentioning
confidence: 93%
“…Thedetailed molecular structure of 3a was determined by X-ray crystallographic analysis, [12] and an ORTEP drawing is shown in Figure 1. To the best of our knowledge,single-crystal X-ray analyses on non-anellated 1,3-azaphospholes have not been reported, although some theoretical studies have revealed structures of 1,3-azaphospholes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Isocyanide compounds added an extra bonus for enlarging the repertoire of accessible molecular scaffolds and have found widespread use in multicomponent reactions, insertion reactions, and other one-pot cascade processes . Among the families, functionalized isocyanides with several reaction centers such as TosMIC, isocyanoacetates, and isocyanoacetamides have become more attractive in recent years and have proven to be a versatile functionality to react with carbonyl compounds, imines, activated alkenes/alkynes, and others . Nevertheless, groups like ester, amide, and tosyl on the isocyanides have not been sufficiently utilized in part of the reactions, as seen in investigation of the related literature.…”
mentioning
confidence: 99%